2011
DOI: 10.1002/rcm.5094
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐specific and spatiotemporal variation of δ13C and δ15N in Charophytes of Lake Constance: implications for food web studies

Abstract: Macrophytes are at the base of many lake food webs providing essential food resources for animals at higher trophic level, such as invertebrates, fish and waterbirds. However, data regarding the spatiotemporal variation in isotopic composition of macrophytes are generally missing. We measured the carbon and nitrogen stable isotope ratios of Charophytes at Lake Constance, where they constitute a major food source for waterbirds. Our data reveal seasonal and site-specific differences as well as depth-specific va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Nevertheless, the temperature in our study was approximately the same as that of the tilapia's natural environment; thus, differences in isotope turnover among tissues could not be linked to a change in temperature. Some researchers have also reported that isotopic turnover rates varied with body size, ontogenetic state and other environmental factors, which were not responsible for the turnover variation in our study. We deduced that the variation in isotopic turnover rates was mainly attributable to the different biochemical compositions of the tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Nevertheless, the temperature in our study was approximately the same as that of the tilapia's natural environment; thus, differences in isotope turnover among tissues could not be linked to a change in temperature. Some researchers have also reported that isotopic turnover rates varied with body size, ontogenetic state and other environmental factors, which were not responsible for the turnover variation in our study. We deduced that the variation in isotopic turnover rates was mainly attributable to the different biochemical compositions of the tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Spatial differences in isotopic signatures are commonly observed between different sites in Lake Constance (e.g. Fuentes, Güde, & Straile 2013;Matuszak, Voigt, Storch, Bauer, & Quillfeldt 2011;Yohannes, Franke, & Rothhaupt 2014). Interestingly however, the four species were not equally affected by inter-habitat isotopic differences [e.g., ␦ 13 C and ␦ 15 N; sampling year 2011 (Table 2) vs. ␦ 13 C and ␦ 15 N; sampling year 2012 (Table 3)].…”
Section: Discussionmentioning
confidence: 97%